Microsoft Azure - Warner, Timothy L. (For Dummies, a Wiley Brand, 2020)
Your roadmap to Microsoft Azure Azure is Microsoft's flagship cloud computing platform. With over 600 services available to over 44 geographic regions, it would take a library of books to cover the entire Azure ecosystem. Microsoft Azure For Dummies offers a shortcut to getting familiar with Azure's core product offerings used by the majority of its subscribers. It's a perfect choice for those looking to gain a quick, basic understanding of this ever-evolving public cloud platform. Written by a Microsoft MVP and Microsoft Certified Azure Solutions Architect, Microsoft Azure For Dummies covers building virtual networks, configuring cloud-based virtual machines, launching and scaling web applications, migrating on-premises services to Azure, and keeping your Azure resources secure and compliant. Migrate your applications and services to Azure with confidence Manage virtual machines smarter than you've done on premises Deploy web applications that scale dynamically to save you money and effort Apply Microsoft's latest security technologies to ensure compliance to maintain data privacy With more and more businesses making the leap to run their applications and services on Microsoft Azure, basic understanding of the technology is becoming essential. Microsoft Azure For Dummies offers a fast and easy first step into the Microsoft public cloud.
Includes index
Keywords: Microsoft Azure (Computing platform); Computing platforms; Cloud computing; Plateformes (Informatique); Infonuagique; Microsoft Azure (Plateforme informatique); handbooks; manuals (instructional materials); Handbooks and manuals; Guides et manuels